Hydrogenation of a model mixture of anthracene with benzothiophene - Gudun, K.A.; Baikenov, M.I.; Feng-yun, Ma (Allerton Press, Inc., 2010)
The reactivity of an anthracene-benzothiophene mixture in the presence of various catalytic additives was studied. The efficiency of the catalytic additives was evaluated from various standpoints.